The Influence of Digital Financial Inclusion Strategy on Digital Economic Transformation of MSMEs in Indonesia - Ginna Novarianti Dwi Putri Pramesti (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
The transformation of the digital economy has become one of the main drivers of economic growth in various developing countries, including Indonesia, where Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economic structure. However, many MSMEs still face limited access to formal financial services and digital technology that can support the business transformation process. This study aims to analyze the influence of digital financial inclusion strategies on the transformation of the MSME digital economy in Indonesia and identify the role of digital financial literacy, regulatory quality, and digital infrastructure in strengthening these relationships. This study uses a mixed-method approach by combining quantitative and qualitative methods. Quantitative data was obtained through a survey of 398 MSMEs in five provinces in Indonesia, while qualitative data was obtained through in-depth interviews and focus group discussions (FGD) with MSME actors and fintech stakeholders. Data analysis was carried out using Structural Equation Modeling (SEM) and thematic analysis to strengthen the interpretation of the research results. The results of the study show that the digital financial inclusion strategy has a positive and significant influence on the transformation of the digital economy of MSMEs, especially through the adoption of digital payments and fintech-based credit access. In addition, digital financial literacy has been proven to play a role as a mediating variable that strengthens the relationship, while the quality of regulation and digital infrastructure serves as a moderation factor that magnifies the impact of digital financial inclusion on the transformation of MSMEs. The implications of this study show that integrated policies between increasing access to digital financial services, strengthening digital financial literacy, and developing supporting infrastructure and regulations are essential to accelerate the digital transformation of MSMEs. This research makes an original contribution by offering an integrated analytical framework that connects digital financial inclusion, digital financial literacy, and institutional factors as the main drivers of the transformation of the MSME digital economy in developing countries.